Informing Implementation Strategies for Pharmacogenomics in Cancer: Development of Survey Tools for Healthcare Professionals and Consumers - Marliese Alexander; Chiao Xin Lim; Senthil Lingaratnam; Sarah Glewis; Joanne Wickens; Abbey Hird; Zi Yue Chen; Alistair Bozkurt; Amit Khot; David Routledge; Sam Harris; Craig Underhill; et al. (Clinical and Translational Science)
ABSTRACT Integration of clinical pharmacogenomics (PGx) within routine cancer care is limited despite frequent use of medicines impacted by PGx, evidence for the benefits of PGx, and the availability of international PGx clinical guidelines. Our study objective was to develop survey tools to assess PGx knowledge, attitudes, practices, perceptions, and education needs among (a) doctors, nurses, and pharmacists involved in cancer care (healthcare professionals, HCPs) and (b) adults who have received cancer treatment or their carers (consumers), with the view to informing implementation strategies for PGx in solid and hematologic cancers. Survey tools were developed in a three‐phase (ph) mixed‐methods approach. Content was informed by systematic literature review findings and framed by determinants of behavior as informed by the Theoretical Domains Framework (ph‐1). Refinement occurred through four separate priority partnership meetings (ph‐2). Meetings focused on clinical PGx practices within select cancer streams, and consumers' knowledge, attitudes, and preferences for PGx testing. Content/face validity and health literacy (Flesch Kincaid Grade Level) assessments informed final refinements (ph‐3). Separate HCP and consumer survey tools were developed with six common sections: (1) introduction; (2) demographics; (3) experience; (4) knowledge, attitudes, practices and perceptions; (5) education; and (6) vignettes. Content and face validity were rated highly with acceptable health literacy assessments for questions within the consumer survey (median grade level 6; range 1–8). The developed survey tools will be used to generate evidence to inform local implementation strategies for PGx in cancer and promote broader integration of pharmacogenomics in routine clinical care.